Implementation of halal product usage categories in science education - Asep Andri; Sri Fitri Solihah; Zulfa Ayu Zahra; Neneng Windayani; Ateng Supriatna (Universitas Ahmad Dahlan, 2026)
Product consumption has increased in line with technological and industrial developments. This study aims to apply halal categories in science education in schools, specifically to improve students' understanding of halal products and their application in everyday life. An interdisciplinary approach is used to integrate scientific concepts with halal literacy through practical activities, discussions, and socialization. Data were obtained through a literature review of articles published between 2017 and 2024 that were relevant to the concepts of halal and halal products. The results of the study show that the application of halal categories in science education not only improves students' understanding of halal products but also encourages them to be more critical in choosing consumer goods. This study also highlights the importance of collaboration between educators, students, and business actors in creating a learning environment that supports halal literacy. Thus, it is hoped that students can contribute to promoting halal products and supporting the growth of the halal industry in Indonesia. Keywords: Halal certification, Halal literacy, Halal product innovation, Project-based learning, Science education